2021
DOI: 10.3389/fonc.2021.722797
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Pathogens Promote Oral Squamous Cell Carcinoma by Regulating ATR and NLRP3 Inflammasome

Abstract: Periodontitis is closely related to oral cancer, but the molecular mechanism of periodontal pathogens involved in the occurrence and development of oral cancer is still inconclusive. Here, we demonstrate that, in vitro, the cell proliferation ability and S phase cells of the periodontitis group (colonized by Porphyromonas gingivalis and Fusobacterium nucleatum, P+) significantly increased, but the G1 cells were obviously reduced. The animal models with an in situ oral squamous cell carcinoma (OSCC) and periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…In pancreatic cancer, Porphyromonas gingivalis is the most studied, and data have shown in murine models that they are able to promote progression of pancreatic cancer ( Chen et al., 2020 ; Gnanasekaran et al., 2020 ; Hiraki et al., 2020 ). Other experimental data have shown that the P. gingivalis may invade and promote proliferation of other cancer types including oral squamous cell carcinoma ( Inaba et al., 2014 ; Geng et al., 2017 ; Chang et al., 2019 ; Hoppe et al., 2019 ; Yao et al., 2021 ), endothelial cancer ( Crooks et al., 2021 ), colorectal carcinoma ( Mu et al., 2020 ; Wang et al., 2021 ), oesophageal squamous cell carcinoma ( Meng et al., 2019 ; Liang et al., 2020 ; Chen et al., 2021 ), and head and neck cancer ( Utispan et al., 2018 ). Further, P. gingivalis has been shown to promote chemotherapy resistance to paclitaxel in oral squamous cell carcinoma ( Song et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, Porphyromonas gingivalis is the most studied, and data have shown in murine models that they are able to promote progression of pancreatic cancer ( Chen et al., 2020 ; Gnanasekaran et al., 2020 ; Hiraki et al., 2020 ). Other experimental data have shown that the P. gingivalis may invade and promote proliferation of other cancer types including oral squamous cell carcinoma ( Inaba et al., 2014 ; Geng et al., 2017 ; Chang et al., 2019 ; Hoppe et al., 2019 ; Yao et al., 2021 ), endothelial cancer ( Crooks et al., 2021 ), colorectal carcinoma ( Mu et al., 2020 ; Wang et al., 2021 ), oesophageal squamous cell carcinoma ( Meng et al., 2019 ; Liang et al., 2020 ; Chen et al., 2021 ), and head and neck cancer ( Utispan et al., 2018 ). Further, P. gingivalis has been shown to promote chemotherapy resistance to paclitaxel in oral squamous cell carcinoma ( Song et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms mainly include the following: disruption of intracellular calcium homeostasis ( 37 ), formation of reactive oxygen species ( 35 ) as well as the disruption of physiological functions like the glutamate-glutamine cycle ( 38 ) or various signaling pathways such as the PI3K/Akt and NF-κB signaling pathway ( 12 , 36 ). Soluble La (III) species have the ability to activate NLRP3 inflammasome, and the latter was regarded as a key mediator of inflammation in promoting the development of oral cancer ( 21 23 ). These findings provide new insight into the action mechanism of La on cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, showed that La has carcinogenic potential when its concentration fluctuates in colorectal and hepatic cancer cells ( 20 ). Of note, a recent study revealed that soluble La (III) species were found to cause NLRP3 inflammasome activation, which has been proved to be a mechanism for promoting oral cancer ( 21 23 ). However, most of those researches were restricted to cell or animal experiments.…”
Section: Introductionmentioning
confidence: 99%
“…These patients showed a higher probability of 32.8% for poorly differentiated OSCC than patients of good oral health at 11.5%. A very recent study by Yao et al [ 214 ] from 2021 developed a new mechanism connecting periodontopathogenic bacteria ( P. gingivalis and F. nucleatum ) and OSCC, by showing that these bacterial species upregulate NLRP3 expression and drive inflammasome activation. It was examined that this pathway can level up tumor growth and tumor proliferation.…”
Section: Oral Squamous Cell Carcinomamentioning
confidence: 99%